Poloxamine/fibrin hybrid hydrogels for non‐viral gene delivery. (1st June 2014) - Zhang, Jeremy; Sen, Atanu; Cho, Eunhee; Lee, Jeoung Soo; Webb, Ken
Abstract: Hydrogels have been widely investigated for localized, sustained gene delivery because of the similarity of their physical properties to native extracellular matrix and their ability to be formed under mild conditions amenable to the incorporation of bioactive molecules. The objective of this study was to develop bioactive hydrogels composed of macromolecules capable of enhancing the efficiency of non‐viral vectors. Hybrid hydrogels were prepared by simultaneous enzymatic and Michael‐type addition crosslinking of reduced fibrinogen and an acrylated amphiphilic block copolymer, Tetronic T904, in the presence of dithiothreitol (DTT) and thrombin. T904/fibrin hydrogels degraded by surface erosion in the presence of plasmin and provided sustained release of polyplex vectors up to an order of magnitude longer than pure fibrin gel control. In addition, the rate of gel degradation and time‐course of polyplex vector release were readily controlled by varying the T904/fibrinogen ratio in the gel composition. When added to transfected neuroblastoma (N2A) cells, both native T904 itself and hydrogel degradation products significantly increased polyplex transfection efficiency with minimal effect on cell viability. To evaluate gel‐based transfection, N2A cells encapsulated in small fibrin clusters were covered by or suspended within polyplex‐loaded hydrogels. Cells progressively degraded and invaded the hybrid hydrogels, exhibiting increasing gene expression over 2 weeks and then diminishing but persistent gene expression for over 1 month. In conclusion, these results demonstrate that T904/fibrin hybrid hydrogels can be promising tissue engineering scaffolds that provide local, controlled release of non‐viral vectors in combination with the generation of bioactive gel degradation products that actively enhance vector efficiency. Copyright © 2014 John Wiley & Sons, Ltd.